(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article deals with the issues of neology and ecolinguistics. The authors specify the criteria of ecolinguistic approach to studying neologisms based on ecolinguistic monitoring which helps to elicit factors that influence the formation of new words, spheres in which they function in language as well as to define the type of new words and number of loanwords among them.